Is the Advanced Cardiac Life Support Algorithm Always Correct? A Case of Catecholaminergic Polymorphic Ventricular Tachycardia - Cillis, Nicole I; Bodziock, George M; Ferris, Taylor S; Patel, Nikhil; Pothuraju, Tejit V; Bhave, Prashant D (British Journal of Healthcare and Medical Research, 2024)
A 19-year-old male with catecholaminergic polymorphic ventricular tachycardia (CPVT) presented with outside-of-hospital cardiac arrest in electrical storm. Ventricular arrhythmias persisted while following the Advanced Cardiac Life Support (ACLS) algorithm using epinephrine boluses. Upon deviation from the ACLS algorithm and use of beta blockers, ventricular arrhythmias ceased and patient was successfully stabilized. Treatment of CPVT electrical storm is challenging due to limited guidelines. Antiarrhythmic agents such as beta blockers and flecainide are among the primary treatment options. This case report highlights a unique example of how deviation from traditional ACLS may be necessary to best treat CPVT storm.